AN An Investigation of Teachers’ Roles in Remote Teaching Context - Ni G.A Made Ari Dharma Pattni; Purnamika Utami , IGA L.; Budiarta, Luh Gd. Rahayu (International Journal of Language and Literature, 2023)
Remote teaching has emerged as an increasingly utilized learning strategy amidst the pandemic in order to mitigate the spread of the COVID-19 virus. Therefore this study aims to analyze the teachers’ roles and their challenges in the context of remote teaching. Moreover, the study was researched by using a qualitative method in which the data will be served descriptively. Specifically, observation and interview methods are used to collect data from two EFL teachers at the senior high school level. Data analysis consist of four process there are data collection, data reduction, data display, and conclusion drawing and verification.The result of this study showed that the teachers implemented eight different roles in the context of remote teaching namely controller, organizer, assessor, prompter, participant, resource, tutor, and observer. Furthermore, in applying for these roles, the teachers also faced some challenges from different categories such as poor connection, low motivation of students, difficulty in sharing and in preparing the learning material, limited access to learning platforms, and difficulty in the assignment process.